PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK, DAN PERSEPSI HARGA TERHADAP KEPUASAN KONSUMEN SUSU SEGAR MOO DI KOTA BANDAR LAMPUNG - Ningrum, Intan Paramiarta; Sayekti, Wuryaningsih Dwi; Adawiyah, Rabiatul (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This study aims to determine purchasing patterns, satisfaction levels, influence of service quality, product quality, and price perceptions of the satisfaction of Moo fresh milk consumers. The research was a survey method conducted at Chandra Department Store, Tanjung Karang. The research samples were recruited by using accidental sampling. There were 50 households of Moo fresh milk consumers, in which respondents of this study were housewives. Data collection was conducted in May-June 2018 and were analyzed by descriptive analysis, Customer Satisfaction Index Analysis (CSI), and verification analysis. The results of this study indicated that the most bought was 1-liter-package type. The volume of purchases of Moo fresh milk was mostly 1-3 litters per month with a frequency of purchases of 1-2 times per month. The score of Moo fresh milk consumer satisfaction was 80.43 percent, meaning that consumers were satisfied. Service quality and product quality had significant effects; while price perception had no significant effect on consumer’s satisfaction of fresh milk Moo. Key words: fresh milk, satisfaction, service quality